Abordagem histórico cultural: resistências e possibilidades de sua aplicação na educação básica - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The research sought to raise resistance to the application of the historical cultural approach in the classroom, as well as verify their possibilities in the pedagogical work through the application of the educational product pedagogical workshop held in the schools surveyed. As a hypothesis of resistance to it were pointed out, the prevalence of traditional teaching in schools, teacher training with the dichotomy theory and practice, and the actual role of the school. It was used a bibliographical review with reading of articles and classic texts cited in the bibliography of each article, also the application of two focal group sections in two schools of the municipal network of Anápolis with the participation of 16 teachers from such schools. The results of the focus groups indicated that there is still a strong presence of traditional teaching in the pedagogical work of the participants and of the schools themselves, that there is a need for theoretical deepening taking into consideration the issue of practice in undergraduate and continuing education, that the school has occupied by roles that are not part of the teaching work, that teachers complain about practical alternatives to their work in the classroom. These factors together serve as resistance to new forms of teaching, including the historical cultural approach. The proposal of this work as an educational product was the realization of two pedagogical workshops one in each school, based on the historical cultural approach and application of its main concepts in the classroom, it was taken into account the use of the ludic in the construction of the zone of development proximal, the importance of teacher and student mediation was emphasized and methodologies were created for the social interaction among students. They were assembled for them toys and games that inserted the historical cultural concepts. This research was divided into three articles, the first addressed the formation of cultural historical theory in the period of the Russian post-revolution of 1917 and the construction of the new man, as well as the influence of pedagogical mediation, neuroscience, inclusive education and Cuban education in the learning teaching process. The second article discussed possible resistances to cultural historical theory as well as the emergence of new paradigms in education. The third paper described the process of applying focus groups in two elementary schools in Annapolis, and discussed their results. The main appendix describes the application of the pedagogical workshops and their results to the participants.
Historical cultural approach: resistances and possibilities of its application in basic education
Keywords: Abordagem histórico cultural; Resistências; Possibilidades; Cultural historical approach; resistances; Possibilities; CIENCIAS HUMANAS::EDUCACAO